6xxx series aluminum alloys produced from mixed recycled aluminum alloy scrap for automotive applications

CN123036397APending Publication Date: 2026-11-03NOVELIS INC(US)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580024391.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2025-03-27
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

另一方面,如AA5182和AA5754的铝合金含有低于0.2 wt.%的Si以及大约0.3 wt.%的Mn和Fe,并且这些5xxx系铝合金与6xxx系铝合金化学不相容,因此无法从混合的5xxx系和6xxx系铝合金废料中有效回收

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123036397A_ABST
    Figure CN123036397A_ABST
Patent Text Reader

Abstract

Described herein are 6xxx series aluminum produced from mixed recycled aluminum alloy scrap and less than 20 wt.% virgin aluminum. Also described herein are methods of producing aluminum alloys from mixed recycled aluminum alloy scrap and less than 20 wt.% virgin aluminum. The aluminum alloys and sheets described herein are suitable for automotive applications.
Need to check novelty before this filing date? Find Prior Art

Description

Cross-references to related applications

[0001] This application claims priority and benefit to U.S. Provisional Patent Application No. 63 / 570,366, filed March 27, 2024, which is hereby incorporated in its entirety by reference for all purposes. Technical Field

[0002] This disclosure relates to the fields of metallurgy, aluminum alloys, aluminum processing, and related areas. In particular, this disclosure generally provides recycled-friendly 6xxx series aluminum alloys produced from mixtures of recycled aluminum alloy scrap sources, and includes excess magnesium (Mg), which can replace existing non-recycle-friendly 5xxx and 6xxx series aluminum alloys. This disclosure also provides various end uses of such products, such as in automotive, transportation, industrial, and other applications. Background Technology

[0003] High-strength aluminum alloys are used in many different applications, particularly those requiring both strength and durability. For example, 6xxx series aluminum alloys are widely used in automotive applications due to their excellent combined properties, including strength-to-weight ratio, formability, weldability, and general corrosion resistance. 6xxx series aluminum alloys are commonly used to replace steel in automotive structural and exterior bodywork applications. Since the density of aluminum alloys is typically about 1 / 2.8 that of steel, using such materials reduces vehicle weight and allows for significant improvements in fuel economy. However, the recyclability of aluminum alloys used in automotive applications is limited because various alloying systems with different compositions are used to produce automotive components with varying properties.

[0004] Currently, there is no single alloy that can be used to produce all parts of a vehicle. Instead, various different alloy systems are used to produce different parts with specific performance requirements (e.g., edging properties, strength, flexibility, recyclability). For example, some 6xxx series aluminum alloys can be used to produce structural components, while some 5xxx series aluminum alloys can be used to produce door interior panels. These components cannot be recycled to produce new aluminum alloys because the sources of recycled materials, which contain varying amounts of alloying elements, are mixed.

[0005] Most high-strength 6xxx series aluminum alloys currently available on the market (e.g., AA6111 and AA6011) are excess Si alloys and include Mg, Si, and Cu as hardening elements. Sufficient Si is required to form Mg2Si phase particles, and the Mn and Fe contents are typically limited to less than 0.28 wt.% and 0.2 wt.%, respectively. On the other hand, aluminum alloys such as AA5182 and AA5754 contain less than 0.2 wt.% Si and approximately 0.3 wt.% Mn and Fe. Furthermore, these 5xxx series aluminum alloys are chemically incompatible with 6xxx series aluminum alloys and therefore cannot be effectively recycled from mixed 5xxx and 6xxx series aluminum alloy scrap.

[0006] To improve circularity and recyclability in the automotive industry, there is a need for new aluminum alloys that can enhance the recyclability of mixed 6xxx and 5xxx series aluminum alloy waste from automotive applications. Summary of the Invention

[0007] The embodiments covered by this disclosure are defined by the claims rather than by the content of this invention. The content of this invention is a high-level summary of various aspects of the invention and introduces some concepts further described in the following detailed description section. This content is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used alone to define the scope of the claimed subject matter. The subject matter should be understood by referring to appropriate portions of the specification throughout, any or all of the drawings, and each claim.

[0008] This document describes an aluminum alloy comprising 0.30–0.80 wt.% Si, 0.20–0.50 wt.% Fe, 0.10–0.60 wt.% Cu, 0.05–0.50 wt.% Mn, 0.80–2.00 wt.% Mg, up to 0.20 wt.% Cr, up to 0.20 wt.% Zn, up to 0.15 wt.% Ti, up to 0.15 wt.% impurities, and Al, wherein the aluminum alloy comprises less than 20 wt.% primary aluminum, and wherein the aluminum alloy comprises Mg2Si phase particles present in an amount of 0.8 wt.% to 3.0 wt.%. In some cases, the aluminum alloy comprises 0.30–0.80 wt.% Si, 0.20–0.40 wt.% Fe, 0.10–0.50 wt.% Cu, 0.05–0.50 wt.% Mn, 0.85–1.60 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities and Al. In some cases, the aluminum alloy comprises 0.30–0.50 wt.% Si, 0.20–0.40 wt.% Fe, 0.30–0.50 wt.% Cu, 0.05–0.20 wt.% Mn, 1.4–1.60 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities and Al. In some cases, the aluminum alloy comprises 0.50–0.70 wt.% Si, 0.20–0.40 wt.% Fe, 0.30–0.50 wt.% Cu, 0.20–0.40 wt.% Mn, 0.85–1.10 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities, and Al. In some cases, the aluminum alloy comprises recycled aluminum alloy scrap, wherein the recycled aluminum alloy scrap comprises one or more of the following: up to 15 wt.% 3xxx series recycled aluminum alloy scrap, up to 30 wt.% 5xxx series recycled aluminum alloy scrap, up to 70 wt.% 6xxx series recycled aluminum alloy scrap, or up to 30 wt.% mixed EOL aluminum alloy scrap.

[0009] In some cases, the aluminum alloy comprises soluble Q-phase particles, wherein after solution heat treatment, the aluminum alloy contains less than 1 wt.% Q-phase particles. In some cases, the aluminum alloy comprises α-Al(FeMn)Si phase particles to Mg2Si phase particles in a ratio of 9:1 or greater. In some cases, the total amount of Fe, Mn, and Cr in the aluminum alloy is at least 0.5 wt.%.

[0010] The aluminum alloy, when tempered at T8x, can have a yield strength of 220 MPa to 300 MPa. In some cases, the aluminum alloy is pre-strained. In some cases, the aluminum alloy is tempered at T4, T6, or T8x. In some cases, the strain of the aluminum alloy is 0.25% to 30%, and the aluminum alloy is substantially free of type A Lüders lines. In some cases, the aluminum alloy exhibits an increase in yield strength from 170 MPa to 270 MPa after being subjected to baking cycles at a temperature of 140°C to 180°C for 10 to 30 minutes.

[0011] This document also describes a method for producing aluminum alloys, the method comprising casting an aluminum alloy to form a cast product, wherein the aluminum alloy comprises 0.30–0.80 wt.% Si, 0.20–0.40 wt.% Fe, 0.10–0.50 wt.% Cu, 0.05–0.50 wt.% Mn, 0.80–1.60 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities and Al, wherein the aluminum alloy comprises less than 20 wt.% primary aluminum; homogenizing the cast product; hot rolling the cast product to produce a hot-rolled product; cold rolling the hot-rolled product to produce a final-gauge rolled product; and solution heat treating the final-gauge rolled product. In some cases, the method further comprises aging the final-gauge rolled product to T tempering. In some cases, the T-tempering is T4 tempering, T6 tempering, or T8x tempering. In some cases, the method further includes pre-straining the final-gauge rolled product after aging. In some cases, the cast product is cast from an aluminum alloy comprising one or more of the following: Twitch, 5xxx aluminum alloy, 6xxx aluminum alloy, or can body stock. In some cases, the final-gauge rolled product comprises Q-phase particles prior to solution heat treatment, and wherein the final-gauge rolled product is solution heat treated at a temperature of 500°C to 580°C for at most 1 minute to dissolve the Q-phase particles, and the final-gauge rolled product is substantially free of Q-phase particles after solution heat treatment. In some cases, the final-size rolled product comprises Mg2Si phase particles prior to solution heat treatment, wherein the final-size rolled product is subjected to solution heat treatment at a temperature of 500°C to 600°C for 5 to 30 minutes to dissolve at least half of the Mg2Si phase particles, and after the solution heat treatment, the final-size rolled product contains 0.8 wt.% to 3 wt.% of Mg2Si phase particles.

[0012] Further aspects, objectives, and advantages will become apparent upon consideration of the following detailed description and accompanying drawings. Attached Figure Description

[0013] Figure 1A-1C Optical microscopic images of the microstructure of example alloy A are shown, these images are taken at the first edge location ( Figure 1A ), central location ( Figure 1B ) and second edge position ( Figure 1C The image was taken along the longitudinal direction of the re-rolled thickness at point ).

[0014] Figure 1D-1FOptical microscopic images of the microstructure of example alloy B are shown, these images are taken at the first edge location ( Figure 1D ), central location ( Figure 1E ) and second edge position ( Figure 1F The image was taken along the longitudinal direction of the re-rolled thickness at point ).

[0015] Figure 2A and 2B An optical microscopic image of the microstructure of example alloy A before solution heat treatment (SHT) is shown. Figure 2A ) and optical microscopic images of the microstructure of example alloy B before solution heat treatment. Figure 2B ).

[0016] Figure 2C and 2D An optical microscopic image of the microstructure of example alloy A after SHT is shown. Figure 2C ) and optical microscopic images of the microstructure of example alloy B after solution heat treatment. Figure 2D ).

[0017] Figure 3A X-ray diffraction patterns of particles extracted from the matrix of Example Alloy B before (F tempering) and after (T4 tempering) are provided.

[0018] Figure 3B X-ray diffraction patterns of particles extracted from the matrix of Example Alloy A before (F tempering) and after (T4 tempering) SHT are provided.

[0019] Figure 4A A graph showing the relative amounts (wt.%) of different particles in the microstructure of example alloy A before (F tempering) and after (T4 tempering) SHT is provided.

[0020] Figure 4B A graph is provided showing the relative amounts (wt.%) of different particles in the microstructure of example alloy B before (F tempering) and after (T4 tempering).

[0021] Figure 5A A graph showing the engineering stress-strain curves of AA5182 aluminum alloy under O tempering is provided.

[0022] Figure 5B A graph showing the engineering stress-strain curves of example alloy B is provided.

[0023] Figure 5C A graph showing the engineering stress-strain curves of example alloy A is provided.

[0024] Figure 6A graph is provided showing the effect of natural aging over time (x-axis, days) on the transverse yield strength (MPa) of Example Alloy A after solution heat treatment at 560 °C and Example Alloy B after solution heat treatment at 535 °C and 550 °C.

[0025] Figure 7A A graph is provided showing the transverse yield strength (MPa) of example alloy B at 535°C SHT.

[0026] Figure 7B A graph is provided showing the transverse yield strength (MPa) of example alloy B at 550°C SHT.

[0027] Figure 7C A graph is provided showing the transverse yield strength (MPa) of example alloy A at 560°C SHT.

[0028] Figure 8A A graph is provided showing the effect of solution heat treatment at 535°C SHT followed by aging at 140°C, 160°C, and 180°C, as well as aging at high temperature for a period of time (x-axis, hours) after T4 tempering on example alloy B.

[0029] Figure 8B A graph is provided showing the effect of solution heat treatment at 550°C SHT followed by aging at 140°C, 160°C, and 180°C, as well as aging at high temperature for a period of time (x-axis, hours) after T4 tempering.

[0030] Figure 8C A graph is provided showing the effects of solution heat treatment at 560°C PMT followed by aging at 140°C, 160°C, and 180°C, as well as aging at high temperature for a period of time (x-axis, hours) after T4 tempering on example alloy A.

[0031] Figures 9A-9B Provided are optical microscopic images of the microstructure of example alloy B, taken longitudinally along the sample thickness. The sample was subjected to solution heat treatment at 550°C and is in a T4 tempered and polished state. Figure 9A ) and grain structure ( Figure 9B ).

[0032] Figure 10A Images of the blank shape of the sheet from example alloy B before stamping are provided.

[0033] Figure 10B Images of a stamped panel after stamping are provided, showing a sheet from example alloy B. Detailed Implementation

[0034] This paper describes a novel aluminum alloy produced from a combination of recycled aluminum alloy scrap sources, exhibiting a good combination of strength and formability. The aluminum alloy described herein can be produced from a combination of recycled aluminum alloy scrap (including can body scrap (CBS), 6xxx series aluminum alloy scrap, 5xxx series aluminum alloy scrap, and Twitch scrap) with a minimum amount of primary aluminum. In some embodiments, the aluminum alloy described herein includes an excess of Mg (e.g., an excess Mg aluminum alloy) and is primarily hardened by Mg₂Si and / or Q second-phase particles. As used herein, an excess Mg aluminum alloy refers to an aluminum alloy with a Mg to Si weight ratio greater than 1:1. Furthermore, the aluminum alloy described herein can tolerate higher levels of Fe, Mn, and Cu dispersions than conventional 6xxx series aluminum alloys, thereby enabling the incorporation of new sources of recycled aluminum alloy scrap (e.g., mixed 5xxx / 6xxx series aluminum alloys). Advantageously, the aluminum alloy described herein improves the recyclability and recyclability of 6xxx series aluminum alloys while still maintaining good strength and formability properties.

[0035] High-strength 6xxx series aluminum alloys are commonly used in strength-critical components, such as in automotive applications or roll forming applications. For example, AA6111 and AA6011 aluminum alloys are used to produce structural components for automobiles. These two 6xxx series aluminum alloys have lower levels of Fe, Mn, and Cr, as well as Mg and Zn, than those found in recycled aluminum alloy scrap sources, because these elements can form coarse particles that are detrimental to formability. Excess Mg present in conventional 6xxx series alloys, exceeding the amount required to form Mg₂Si phase particles, can reduce the solubility of those particles during solution heat treatment and can negatively impact age hardening. However, various 5xxx and 6xxx series aluminum alloy scrap sources contain higher levels of Fe, Mn, Cr, Mg, and Zn than conventional 6xxx series alloys, limiting their use in the production of conventional 6xxx series alloys (and thus reducing recyclability and recyclability).

[0036] The aluminum alloys described herein offer an alternative to conventional 6xxx series aluminum alloys. Advantageously, the aluminum alloys described herein provide cleaner, more uniform 6xxx series aluminum alloys, which improve the recyclability and recyclability of high-strength 6xxx series aluminum alloys. Specifically, this disclosure provides a 6xxx series aluminum alloy comprising excess Mg (0.85 to 2.00 wt.%), which exhibits good strength and formability properties. The aluminum alloys described herein can be produced from mixtures of different 6xxx series aluminum alloys, mixtures of 5xxx and 6xxx series aluminum alloy scrap, and other types of recycled aluminum alloy scrap without separation or sorting, a major obstacle to recycling. Furthermore, the composition window of the aluminum alloys described herein is fine-tuned to accept high recycled content (e.g., less than 20 wt.% primary aluminum). Additionally, the aluminum alloys described herein allow for easier management of recycled aluminum alloy scrap and provide a low carbon footprint for end users.

[0037] The aluminum alloy compositions described herein offer a combination of good mechanical properties and low primary aluminum content as an alternative to existing high-strength 6xxx series aluminum alloys. The aluminum alloys can be produced from at least 80 wt.% recycled aluminum alloy material. In some embodiments, the aluminum alloys described herein comprise 0.2 wt.% to 0.5 wt.% Fe and 0.05 wt.% to 0.5 wt.% Mn, with the balance being Si, Mg, and Cu, such that the age hardening of the aluminum alloy is dominated by Mg2Si, quaternary Q, and / or Al2CuMg second-phase particles. Therefore, the alloys described herein are designed to absorb a variety of recycled aluminum alloy scrap sources, including 3xxx series recycled aluminum alloy scrap, 5xxx series recycled aluminum alloy scrap, 6xxx series recycled aluminum alloy scrap, mixed end-of-life (“EOL”) aluminum alloy scrap, can body scrap (CBS) recycled edge scrap (RAR) scrap, Twitch, mixed 5xxx and 6xxx series aluminum alloy scrap, or combinations thereof.

[0038] Definition and description As used herein, the terms “invention,” “the invention,” “this invention,” and “the present invention” are intended to broadly refer to the subject matter of this patent application and all of the following claims. Statements containing these terms should not be construed as limiting the subject matter described herein or limiting the meaning or scope of the patent claims below.

[0039] In this specification, references are made to alloys identified by aluminum industry designations such as "series" or "6xxx". For an understanding of the most commonly used numerical designation systems in naming and identifying aluminum and its alloys, see "International Alloy Designations and Chemical Composition Limits for Wrought Aluminum and Wrought Aluminum Alloys" or "Registration Record of Aluminum Association Alloy Designations and Chemical Composition Limits for Aluminum Alloys in the Form of Castings and Ingot", both published by the Aluminum Association.

[0040] As used herein, unless the context clearly indicates otherwise, “a” or “the” means both singular and plural referents.

[0041] As used herein, the thickness of a sheet is typically greater than about 15 mm. For example, a sheet may refer to an aluminum product having a thickness greater than about 15 mm, greater than about 20 mm, greater than about 25 mm, greater than about 30 mm, greater than about 35 mm, greater than about 40 mm, greater than about 45 mm, greater than about 50 mm, or greater than about 100 mm.

[0042] As used in this article, shate (also known as sheet board) typically has a thickness of about 4 mm to about 15 mm. For example, shate can have a thickness of about 4 mm, about 5 mm, about 6 mm, about 7 mm, about 8 mm, about 9 mm, about 10 mm, about 11 mm, about 12 mm, about 13 mm, about 14 mm or about 15 mm.

[0043] As used in this article, sheet material generally refers to aluminum products with a thickness of less than about 4 mm (e.g., less than 3 mm, less than 2 mm, less than 1 mm, less than 0.5 mm, less than 0.3 mm, or less than 0.1 mm). For example, the sheet may have a thickness of about 0.1 mm, about 0.2 mm, about 0.3 mm, about 0.4 mm, about 0.5 mm, about 0.6 mm, about 0.7 mm, about 0.8 mm, about 0.9 mm, about 1 mm, about 1.1 mm, about 1.2 mm, about 1.3 mm, about 1.4 mm, about 1.5 mm, about 1.6 mm, about 1.7 mm, about 1.8 mm, about 1.9 mm, about 2 mm, about 2.1 mm, about 2.2 mm, about 2.3 mm, about 2.4 mm, about 2.5 mm, about 2.6 mm, about 2.7 mm, about 2.8 mm, about 2.9 mm, about 3 mm, about 3.1 mm, about 3.2 mm, about 3.3 mm, about 3.4 mm, about 3.5 mm, about 3.6 mm, about 3.7 mm, about 3.8 mm, about 3.9 mm, or about 4 mm.

[0044] As used herein, formability refers to the ability of a material to be deformed into a desired shape without fracture, tearing, necking, lugging, or forming errors such as wrinkling, springback, or burring. In engineering, formability can be classified according to deformation modes. Deformation modes include drawing, stretching, bending, and stretch flanging.

[0045] This application may refer to alloy tempering or tempering. For the most commonly used descriptions of alloy tempering, see “American National Standards (ANSI) H35 on Alloy and Temper Designation Systems”. F tempering refers to manufactured aluminum alloys. O tempering refers to annealed aluminum alloys. Hxx tempering, also referred to herein as H tempering, refers to non-heat-treatable aluminum alloys that have been cold-rolled and may or may not have undergone heat treatment (e.g., annealing). Suitable H temperings include HX1, HX2, HX3, HX4, HX5, HX6, HX7, HX8, or HX9 temperings. T1 tempering refers to aluminum alloys cooled from hot working and subjected to natural aging (e.g., at room temperature). T2 tempering refers to aluminum alloys cooled from hot working, cold-worked, and subjected to natural aging. T3 tempering refers to aluminum alloys that have undergone solution heat treatment, cold working, and natural aging. T4 tempering refers to aluminum alloys that have undergone solution heat treatment and natural aging. T5 temper or tempered refers to aluminum alloys that have been cooled from hot working and undergone artificial aging (at high temperature). T6 temper or tempered refers to aluminum alloys that have undergone solution heat treatment and artificial aging. T7 temper or tempered refers to aluminum alloys that have undergone solution heat treatment and artificial aging. T8x temper or tempered refers to aluminum alloys that have undergone solution heat treatment, cold working, and artificial aging. T9 temper or tempered refers to aluminum alloys that have undergone solution heat treatment, artificial aging, and cold working. W temper or tempered refers to aluminum alloys after solution heat treatment.

[0046] As used herein, "room temperature" can mean a temperature from about 15°C to about 30°C, such as about 15°C, about 16°C, about 17°C, about 18°C, about 19°C, about 20°C, about 21°C, about 22°C, about 23°C, about 24°C, about 25°C, about 26°C, about 27°C, about 28°C, about 29°C, or about 30°C.

[0047] All ranges disclosed herein should be understood to encompass both endpoints and any and all subranges included therein. For example, the range “1 to 10” should be considered to include any and all subranges between the minimum value 1 and the maximum value 10 (and including the endpoints); that is, all subranges begin with a minimum value of 1 or a number greater than 1, such as 1 to 6.1, and end with a maximum value of 10 or a number less than 10, such as 5.5 to 10.

[0048] The following aluminum alloys are described in terms of elemental composition as a percentage by weight (wt.%) based on the total weight of the alloy. In some instances of each alloy, the remainder is aluminum, and the total amount of impurities is at most 0.15% by weight.

[0049] Alloy composition The properties of aluminum alloys are partly determined by their composition. In some respects, the alloy composition can influence or even determine whether the alloy will possess properties sufficient for the desired application.

[0050] This article describes novel 6xxx series aluminum alloys. The properties of the aluminum alloys are achieved through alloy composition and / or manufacturing methods.

[0051] In some instances, aluminum alloys as described herein may have the following elemental composition as provided in Table 1.

[0052] Table 1

[0053] In some instances, aluminum alloys as described herein may have the following elemental compositions as provided in Table 2.

[0054] Table 2

[0055] In some instances, aluminum alloys as described herein may have the following elemental compositions as provided in Table 3.

[0056] Table 3

[0057] In some instances, aluminum alloys as described herein may have the following elemental compositions as provided in Table 4.

[0058] Table 4

[0059] It should be understood that in the various embodiments of the alloys described herein, including those in Tables 1-4, the primary element is aluminum (Al), sometimes referred to as "balance Al". In other words, the term "balance" can be used to describe the primary aluminum (Al) content in the aluminum alloys described herein.

[0060] Silicon (Si) In some instances, the aluminum alloys described herein comprise 0.30% to 0.80% (e.g., 0.30% to 0.50%, 0.40% to 0.80%, 0.50% to 0.80%, 0.50% to 0.70%, or 0.60% to 0.80%) of Si based on the total weight of the alloy. For example, the alloy may comprise 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.5 4%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, or 0.80% Si. All are expressed in wt.%.

[0061] Iron (Fe) In some instances, the aluminum alloys described herein also include 0.20% to 0.50% (e.g., 0.20% to 0.40%, 0.20% to 0.30%, or 0.25% to 0.35%) of Fe based on the total weight of the alloy. For example, the alloy may include 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, or 0.50% Fe. All are expressed in wt.%.

[0062] Copper (Cu) In some instances, the aluminum alloys described herein comprise 0.10% to 0.60% (e.g., 0.15% to 0.50%, 0.20% to 0.50%, or 0.30% to 0.50%) of Cu based on the total weight of the alloy. For example, the alloy may comprise 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.3% Cu. 4%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, or 0.60% Cu. All are expressed in wt.%.

[0063] Manganese (Mn) In some instances, the aluminum alloys described herein may include an amount of Mn of 0.05% to 0.50% (e.g., 0.05% to 0.40%, 0.05% to 0.20%, or 0.20% to 0.40%) based on the total weight of the alloy. For example, the alloy may include 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, or 0.40% Mn. All values ​​are expressed in wt.%.

[0064] Magnesium (Mg) In some instances, the aluminum alloys described herein may include 0.80% to 2.00% (e.g., 0.80% to 1.60%, 0.85% to 1.10%, or 1.40% to 1.60%) of Mg based on the total weight of the alloy. For example, the alloy may include 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00%, 1.01%, 1.02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1. 0.8%, 1.09%, 1.10%, 1.11%, 1.12%, 1.13%, 1.14%, 1.15%, 1.16%, 1.17%, 1.18%, 1.19%, 1.20%, 1.21%, 1.22%, 1.23%, 1.24%, 1.25%, 1.26%, 1.28%, 1.29%, 1.30%, 1.31%, 1.32%, 1.33%, 1.34%, 1.35%, 1.36%, 1.37%, 1.38%, 1.3 9%, 1.40%, 1.41%, 1.42%, 1.43%, 1.44%, 1.45%, 1.46%, 1.47%, 1.48%, 1.49%, 1.50%, 1.51%, 1.52%, 1.53%, 1.54%, 1.55%, 1.56%, 1.57%, 1.58%, 1.59%, 1.60%, 1.61%, 1.62%, 1.63%, 1.64%, 1.65%, 1.66%, 1.67%, 1.68%, 1.69% %, 1.70%, 1.71%, 1.72%, 1.73%, 1.74%, 1.75%, 1.76%, 1.77%, 1.78%, 1.79%, 1.80%, 1.81%, 1.82%, 1.83%, 1.84%, 1.85%, 1.86%, 1.87%, 1.89%, 1.90%, 1.91%, 1.92%, 1.93%, 1.94%, 1.95%, 1.96%, 1.97%, 1.98%, 1.99%, or 2.00% Mg. All are expressed in wt.%. The aluminum alloys described herein are excess Mg aluminum alloys. In other words, the aluminum alloys contain more Mg than is required to form stoichiometric Mg₂Si. Unrestricted by theory, excess Mg contributes to the amount of insoluble Mg2Si phase particles present in aluminum alloys after solution heat treatment, and hardening can be achieved through the precipitation of Al2CuMg / Q and / or Mg2Si / Q phase particles.In some embodiments, the weight ratio of Mg to Si content is greater than 1:1 to 5:1 (e.g., 2:1, 3:1, or 4:1). In some aspects, the weight ratio of Mg to Si content is 1.8 to 4.9 (e.g., 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, or 4.9). In some embodiments, Mg2Si phase particles are present in the alloy in an amount of up to 3 wt.% (e.g., up to 1 wt.%, up to 2 wt.%, or up to 3 wt.%). In some aspects, Mg₂Si phase particles are present in the alloy in an amount of 0.8 wt.% to 3.0 wt.% (e.g., 0.9 wt.% to 2.9 wt.%, 1.1 wt.% to 2.8 wt.%, 1.3 wt.% to 2.7 wt.%, 1.4 wt.% to 3.0 wt.%, 1.5 wt.% to 2.6 wt.%, or 1.7 wt.% to 2.5 wt.%). In some aspects, the weight ratio of α-Al(FeMn)Si phase particles to Mg₂Si phase particles is 4:1 to 9:1. In some aspects, the weight ratio of α-Al(FeMn)Si phase particles to Mg₂Si phase particles is 9:1 or greater.

[0065] Zinc (Zn) In some instances, the aluminum alloys described herein comprise up to 0.15% (e.g., up to 0.12%, 0.09%, 0.07%, 0.05%, 0.03%, or 0.01% to 0.05%) of Zn based on the total weight of the alloy. For example, the alloy may comprise 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, or 0.15% Zn. In some cases, Zn is not present in the alloy (i.e., 0%). All figures are expressed in wt.%.

[0066] Titanium (Ti) In some instances, the aluminum alloys described herein include up to 0.15% (e.g., up to 0.12%, 0.09%, 0.07%, 0.05%, 0.03%, or 0.01% to 0.05%) of Ti based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, or 0.15% Ti. In some cases, Ti is absent from the alloy (i.e., 0%). All figures are expressed in wt.%.

[0067] Chromium (Cr) In some instances, the aluminum alloys described herein include up to 0.20% (e.g., up to 0.15%, up to 0.12%, 0.09%, up to 0.07%, up to 0.05%, up to 0.03%, or 0.01% to 0.05%) of Cr based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.20% Cr. In some cases, Cr is absent in the alloy (i.e., 0%). All figures are expressed in wt.%.

[0068] Trace elements Optionally, the aluminum alloys described herein may further include other trace elements (sometimes referred to as impurities) in amounts of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. These impurities may include, but are not limited to, Ti, Sc, V, Ni, Hf, Zr, Sn, Ga, Ca, Bi, Na, Pb, Sr, B, C, or combinations thereof. Thus, Ti, Sc, V, Ni, Hf, Zr, Sn, Ga, Ca, Bi, Na, Pb, Sr, B, or C may be present in the alloy in amounts of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. The sum of all impurities shall not exceed 0.15% (e.g., 0.1%). All are expressed in wt.%. The remaining percentage of each alloy may be aluminum.

[0069] performance In some instances, aluminum alloy products manufactured from the aluminum alloys described herein may have a yield strength of 100 MPa or greater when subjected to T4 tempering. For example, aluminum alloy products manufactured from the aluminum alloys described herein may have a yield strength of 110 MPa or greater, 120 MPa or greater, 130 MPa or greater, or 140 MPa or greater when subjected to T4 tempering. In some cases, the yield strength when subjected to T4 tempering is 100 MPa to 140 MPa (e.g., 110 MPa to 140 MPa, 120 MPa to 140 MPa, or 130 MPa to 140 MPa), or any value between these values. The aluminum alloy products described herein may exhibit the yield strength described herein when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions, each relative to the rolling direction.

[0070] In some instances, aluminum alloy products manufactured from the aluminum alloys described herein may have an ultimate tensile strength of approximately 200 MPa or greater when subjected to T4 tempering. For example, the aluminum alloy products may have an ultimate tensile strength of 210 MPa or greater, 220 MPa or greater, 230 MPa or greater, 240 MPa or greater, 250 MPa or greater, 255 MPa or greater, 260 MPa or greater, 265 or greater, 270 or greater, 275 or greater, or 280 or greater when subjected to T4 tempering. In some cases, the ultimate tensile strength is between 200 MPa and 300 MPa (e.g., 210 MPa to 300 MPa, 215 MPa to 280 MPa, or 220 MPa to 280 MPa), or any value between these values ​​when subjected to T4 tempering. The aluminum alloy products described herein exhibit the ultimate tensile strength described herein when measured in the longitudinal (L), transverse (T) and / or diagonal (D) directions, each relative to the rolling direction.

[0071] In some instances, aluminum alloy products manufactured from the aluminum alloys described herein may have a total elongation of 15% or greater when tempered at T4. For example, aluminum alloy products manufactured from the aluminum alloys described herein may have a total elongation of 16% or greater, 17% or greater, 18% or greater, 19% or greater, 20% or greater, 21% or greater, 22% or greater, 23% or greater, 24% or greater, 25% or greater, 26% or greater, 28% or greater, or 29% or greater when tempered at T4. In some cases, the total elongation at T4 is 20% to 30% (e.g., 20% to 30%, 21% to 30%, 22% to 30%, 23% to 30%, 24% to 30%, or 25% to 23%), or any value between these values. The aluminum alloy products described herein can exhibit the total elongation described herein when measured in the longitudinal (L), transverse (T) and / or diagonal (D) directions, each relative to the rolling direction.

[0072] In some instances, aluminum alloy products manufactured from the aluminum alloys described herein may have a uniform elongation of 20% or greater when tempered at T4. For example, aluminum alloy products manufactured from the aluminum alloys described herein may have a uniform elongation of 18% or greater, 19% or greater, 20% or greater, 21% or greater, 22% or greater, 23% or greater, or 24% or greater when tempered at T4. In some cases, the uniform elongation at T4 is 18% to 28% (e.g., 19% to 28%, 20% to 28%, 21% to 28%, 22% to 28%, 23% to 26%, or 23% to 25%), or any value between these values. The aluminum alloy products described herein may exhibit the uniform elongation described herein when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions, each relative to the rolling direction.

[0073] In some instances, aluminum alloy products manufactured from the aluminum alloys described herein may have a bending angle of 90° to 145° (e.g., 90° to 140°, 90° to 130°, or 90° to 120°) when subjected to T4 tempering and 10% pre-strain, as measured according to the test measurements described in German Association of the Automotive Industry (VDA) test number 238-100. For example, aluminum alloy products manufactured from the aluminum alloys described herein may have a VDA bending angle of approximately 90°, 95°, 100°, 105°, 110°, 115°, 120°, 125°, 130°, 135°, 140°, or 145°, or any value in between, when subjected to T4 tempering and 10% pre-strain.

[0074] In some instances, aluminum alloy products (e.g., aluminum alloy sheets) produced from the aluminum alloys described herein may have a yield strength of 200 MPa or greater when tempered at T8x. For example, aluminum alloy products produced from the aluminum alloys described herein may have a yield strength of 220 MPa or greater, 230 MPa or greater, 240 MPa or greater, 250 MPa or greater, 260 MPa or greater, 270 MPa or greater, or 280 MPa or greater when tempered at T8x. In some cases, the yield strength when tempered at T8x is 200 MPa to 300 MPa (e.g., 200 MPa to 280 MPa, 220 MPa to 290 MPa, 240 MPa to 280 MPa, or 250 MPa to 275 MPa), or any value in between. The aluminum alloy products described herein exhibit the yield strength described herein when measured in the longitudinal (L), transverse (T) and / or diagonal (D) directions, each relative to the rolling direction.

[0075] In some instances, aluminum alloy products manufactured from the aluminum alloys described herein may have an ultimate tensile strength of approximately 280 MPa or greater upon T8x tempering. For example, the aluminum alloy products may have an ultimate tensile strength of 290 MPa or greater, 300 MPa or greater, 310 MPa or greater, 320 MPa or greater, or 330 MPa or greater upon T8x tempering. In some cases, the ultimate tensile strength is between 280 MPa and 340 MPa (e.g., 290 MPa to 335 MPa, 295 MPa to 330 MPa, or 300 MPa to 325 MPa), or any value between these values. The aluminum alloy products described herein may exhibit the ultimate tensile strength described herein when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions, each relative to the rolling direction.

[0076] In some instances, aluminum alloy products manufactured from the aluminum alloys described herein may have a total elongation of 6% or greater when tempered at T8x. For example, aluminum alloy products manufactured from the aluminum alloys described herein may have a total elongation of 7% or greater, 8% or greater, or 9% or greater when tempered at T8x. In some cases, the total elongation at T8x tempering is 6% to 24% (e.g., 7% to 23%, 8% to 22%, 9% to 21%, 10% to 20%, 11% to 19%, 12% to 18%, or 13% to 17%), or any value between these values. The aluminum alloy products described herein may exhibit the total elongation described herein when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions, each relative to the rolling direction.

[0077] Methods for manufacturing aluminum alloys The aluminum alloys described herein can be cast into cast products using a direct cooling (DC) process or a continuous casting (CC) process. The casting process is performed according to standards commonly used in the aluminum industry as known to those skilled in the art. The CC process may include, but is not limited to, the use of a twin-belt casting machine, a twin-roll casting machine, or a block casting machine. In some instances, the casting process is performed using the CC process to form slabs, strips, etc. In some instances, the casting process is a DC casting process to form cast products.

[0078] Further processing steps can then be performed on the cast product, slab, or strip. Optionally, these further processing steps can be used to prepare aluminum alloy products (e.g., sheets, plates, or plates). Such processing steps include, but are not limited to, homogenization steps, hot rolling steps, cold rolling steps, and optional continuous annealing and solution heat treatment (SHT) steps. These processing steps are described below with respect to cast products. However, with modifications known to those skilled in the art, these processing steps can also be used on slabs or strips.

[0079] In the homogenization step, the cast product can be heated to a homogenization temperature, such as 500°C to 580°C (e.g., 500°C to 580°C, 540°C to 580°C, 550°C to 575°C, 560°C to 570°C). For example, the cast product can be heated to temperatures of 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, and 580°C. In some embodiments, the homogenization temperature is greater than 550°C. The cast product can then be immersed (i.e., held at an indicated temperature) for a period of time to form a homogenized product. In some instances, the total time of the homogenization step (including the heating and immersion stages) can be up to 10 hours. In some instances, the total time of the homogenization step (including the heating and immersion stages) can be up to 48 hours.

[0080] Following the homogenization step, a hot rolling step can be performed. In some embodiments, the homogenized product is hot rolled directly after homogenization. The entry temperature for the hot rolling step can be the same as the homogenization temperature. In some embodiments, the entry temperature before hot rolling is close to the homogenization temperature (e.g., between 500°C and 580°C). In some embodiments, the homogenized product can be cooled before hot rolling begins. The homogenized product can be hot rolled using a rolling mill to produce a hot-rolled product. The homogenized product can be hot-rolled at a temperature ranging from 400°C to 580°C (e.g., 410°C to 590°C, 420°C to 580°C, 430°C to 570°C, 440°C to 560°C, 450°C to 550°C, 460°C to 560°C, 530°C to 555°C, or 530°C to 550°C). For example, the homogenized product can be hot-rolled at hot rolling temperatures of 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, or 580°C.

[0081] The hot-rolled product can be cold-rolled into a thinner product, such as a final-gauge rolled product, using a cold rolling mill. The final-gauge rolled product can have a gauge between 0.5 mm and 10 mm, for example, between 0.7 mm and 6.5 mm. Optionally, the final-gauge rolled product can have the following gauges: 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, 7.0 mm, 7.5 mm, 8.0 mm, 8.5 mm, 9.0 mm, 9.5 mm, or 10.0 mm. Cold rolling can be performed to obtain a final dimensional thickness, which represents a reduction of up to 85% in dimensional thickness compared to the dimensional thickness prior to the start of cold rolling (e.g., a reduction of up to 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 85%). In some embodiments, the cold rolling step may include one or more cold rolling steps to achieve the desired dimensional thickness reduction. Optionally, the process for producing the aluminum alloy may include an intermediate annealing step (e.g., between one or more cold rolling steps).

[0082] After hot or cold rolling, the final-gauge rolled product can be subjected to solution heat treatment. For example, the final-gauge rolled product can be heated to a peak metal temperature (directly after cold rolling) for solution heat treatment. The solution heat treatment step may include heating the final-gauge rolled product from room temperature to a peak metal temperature of 400°C to 580°C (e.g., 420°C to 580°C, 440°C to 570°C, 450°C to 570°C, 460°C to 570°C, 470°C to 570°C, 480°C to 570°C, or 500°C to 570°C). The final-gauge rolled product may be immersed at the peak metal temperature for a period of time. In some aspects, the final-gauge rolled product is allowed to be immersed at the peak metal temperature for up to about 1 minute (e.g., 0 seconds to 60 seconds inclusive). For example, the final-gauge rolled product may be immersed for 0 seconds, 5 seconds, 10 seconds, 15 seconds, 20 seconds, 25 seconds, 30 seconds, 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, 60 seconds, or any value between therebetween, at a peak metal temperature between 500°C and 550°C. In some embodiments, the solution heat treatment step includes immersing the final-gauge rolled product at a peak metal temperature between 515°C and 560°C for 0 to 30 seconds. In some embodiments, the final-gauge rolled product comprises Q-phase particles prior to solution heat treatment, and the final-gauge rolled product is subjected to solution heat treatment at a temperature between 500°C and 580°C for up to 1 minute to dissolve the Q-phase particles, and the final-gauge rolled product contains less than 1 wt.% Q-phase particles after the solution heat treatment. In some aspects, the final-gauge rolled product comprises iron-containing particles, such as α-Al(Fe,Mn,Cu)Si, Q, and Mg2Si phase particles, prior to solution heat treatment, and does not contain Q phase and / or Mg2Si particles after solution heat treatment. In some embodiments, the final-gauge rolled product comprises Al2CuMg phase particles prior to solution heat treatment, and the final-gauge rolled product is solution heat treated at a temperature of 500°C to 580°C for at most 1 minute to dissolve the Al2CuMg phase particles, and the final-gauge rolled product contains less than 1 wt.% of Al2CuMg phase particles after solution heat treatment. In some embodiments, the final-gauge rolled product comprises Mg2Si phase particles prior to solution heat treatment, and the final-gauge rolled product is solution heat treated at a temperature of 500°C to 580°C for at most 1 minute to dissolve most of the Mg2Si phase particles, and the final-gauge rolled product contains at most 3 wt.% of Mg2Si phase particles after solution heat treatment.In some embodiments, the final-size rolled product comprises Mg2Si phase particles prior to solution heat treatment, and the final-size rolled product is subjected to solution heat treatment at a temperature of 500°C to 580°C for up to 1 minute to dissolve most of the Mg2Si phase particles, and the final-size rolled product contains 0.8 wt.% to 3.0 wt.% Mg2Si phase particles after solution heat treatment.

[0083] In some aspects, the final-gauge rolled product is air-cooled or quenched after heat treatment. For example, the final-gauge rolled product may be directly quenched after immersion at the peak metal temperature during a solution heat treatment step. The aluminum alloy may be quenched with air or water. In some embodiments, the quenching rate is from 5°K / s to 200°K / s.

[0084] In some aspects, the final-specification rolled product is aged to temper. The final-specification rolled product may be naturally aged or artificially aged for a period of time to produce a T-temper. For example, the final-specification rolled product may be aged to T4 temper, T6 temper, or T81 temper. In some aspects, the final-specification rolled product provided under T6 temper may be artificially aged (AA) for a period of time at 160°C to 250°C (e.g., 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, or 250°C). Optionally, the final specification rolled product can be artificially aged for a period of 15 minutes to 8 hours (e.g., 15 minutes, 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours or any value in between) to produce T6 tempering or T7 tempering.

[0085] The aluminum alloys described herein are suitable for manufacturing products through plastic forming processes such as creep forming, roll forming, and stretch forming. For example, the aluminum alloys described herein can produce roll-formed products. The aluminum alloys described herein are particularly suitable for roll forming applications, in which aluminum alloy sheets are continuously bent through a series of rolls to produce roll-formed products.

[0086] Recycled component content alloy The aluminum alloys described herein can be produced from a substantial proportion of recycled aluminum alloy scrap. In some embodiments, the aluminum alloys described herein can be produced from a combination of different recycled aluminum alloy scrap materials. Recycled aluminum alloy scrap (e.g., recycled waste) can be obtained from a variety of sources throughout all stages of the aluminum lifecycle. In some cases, recycled aluminum alloy scrap can refer to a collection of recycled metals. Recycled aluminum alloy scrap can include materials recovered from any suitable source, such as from metal production facilities (e.g., metal foundries), from metal processing plants (e.g., production facilities that use metal products to produce consumer goods), or from post-consumer sources (e.g., regional recycling facilities). For example, internal scrap can be generated during the production of aluminum alloys in a metal foundry (e.g., scrap from the production of aluminum ingots, billets, sheets, plates, etc.), customer scrap can be generated during stamping, milling, and other processes in a metal processing plant (e.g., scrap from the manufacture of cans, can lids, automotive parts, etc.), and post-consumer scrap can be generated from aluminum products used by consumers and collected at regional recycling facilities (e.g., used beverage cans, used automotive parts, etc.). Each of these types of recycled aluminum alloy scrap can serve as a substitute for primary aluminum.

[0087] The aluminum alloys described herein can withstand high contents of recycled aluminum alloy scrap while still exhibiting the desired mechanical properties. By providing a specific aluminum alloy composition to compensate for impurities, the impact of impurities and / or alloying elements on the mechanical properties of the aluminum alloy is reduced. This allows for the production of aluminum alloys that still exhibit the desired properties using larger quantities of cheaper aluminum scrap with higher impurity content.

[0088] In some aspects, the aluminum alloy may be produced from up to 100 wt.% recycled aluminum alloy scrap (e.g., 70 wt.% to 100 wt.%, 75 wt.% to 100 wt.%, 80 wt.% to 100 wt.%, or 90 wt.% to 100 wt.%) based on the total weight of the aluminum alloy. In some instances, the aluminum alloy may be produced from 3xxx series recycled aluminum alloy scrap, 5xxx series recycled aluminum alloy scrap, 6xxx series recycled aluminum alloy scrap, mixed end-of-life (“EOL”) aluminum alloy scrap, or combinations thereof. In some aspects, 3xxx series recycled aluminum alloy scrap, 5xxx series recycled aluminum alloy scrap, 6xxx series recycled aluminum alloy scrap, and / or mixed EOL recycled aluminum alloy scrap may have the following elemental composition (in weight percentage) provided in Table 5 below.

[0089] In some embodiments, the aluminum alloy may be produced from up to 20 wt.% of 3xxx series recycled aluminum alloy scrap (e.g., up to 5 wt.%, up to 10 wt.%, or up to 15 wt.%). All are expressed in wt. wt.%. In some embodiments, the aluminum alloy may be produced from up to 40 wt.% of 5xxx series recycled aluminum alloy scrap (e.g., up to 10 wt.%, up to 20 wt.%, or up to 30 wt.%). All are expressed in wt. wt.%. In some embodiments, the aluminum alloy may be produced from up to 80 wt.% of 6xxx series aluminum alloy scrap (e.g., up to 25 wt.%, up to 50 wt.%, up to 70 wt.%, or up to 75 wt.%). All are expressed in wt. wt.%. In some embodiments, the aluminum alloy may be produced from up to 35 wt.% mixed with EOL recycled aluminum alloy scrap (e.g., up to 5 wt.%, up to 10 wt.%, up to 15 wt.%, up to 20 wt.%, up to 25 wt.%, or up to 30 wt.%).

[0090] In some embodiments, the aluminum alloy can be produced from up to 25 wt.% separated Twitch recycled aluminum alloy scrap (e.g., up to 15 wt.% or up to 20 wt.%). For example, the aluminum alloy can be produced from 5 wt.% to 30 wt.% separated Twitch (e.g., 5 wt.% to 25 wt.%, 10 wt.% to 25 wt.%, 15 wt.% to 25 wt.%, or 20 wt.% to 30 wt.%).

[0091] In some embodiments, the aluminum alloy may be produced from up to 25 wt.% of recycled waste material containing 5xxx / 6xxx series aluminum alloy scrap (e.g., up to 15 wt.% or up to 20 wt.%). For example, the aluminum alloy may be produced from 5 wt.% to 25 wt.% of recycled waste material containing 5xxx / 6xxx series aluminum alloy scrap (e.g., 5 wt.% to 25 wt.%, 10 wt.% to 25 wt.%, 15 wt.% to 25 wt.%, or 20 wt.% to 25 wt.%).

[0092] In some embodiments, the aluminum alloy can be produced from up to 15 wt.% of can body stock (CBS) recycled scrap (RAR) aluminum alloy scrap (e.g., up to 5 wt.% or up to 10 wt.%). For example, the aluminum alloy can be produced from 5 wt.% to 25 wt.% of can body stock recycled scrap (RAR) aluminum alloy scrap (e.g., 1 wt.% to 15 wt.%, 5 wt.% to 15 wt.%, 10 wt.% to 15 wt.%, or 0 wt.% to 10 wt.%).

[0093] In some embodiments, primary aluminum may be used in combination with recycled aluminum alloy scrap to produce the aluminum alloys described herein. For example, up to 20 wt.% of primary aluminum (e.g., up to 18 wt.%, up to 15 wt.%, up to 12 wt.%, up to 10 wt.%, up to 8 wt.%, up to 6 wt.%, up to 4 wt.%, up to 2 wt.%, or up to 1 wt.%) may be used to produce the aluminum alloys described herein. All are expressed in wt.%. In some embodiments, the primary aluminum alloy is not used in combination with recycled aluminum alloy scrap.

[0094] Appropriate methods and instructions for alloy products Description 1 is an aluminum alloy comprising 0.30–0.80 wt.% Si, 0.20–0.50 wt.% Fe, 0.10–0.60 wt.% Cu, 0.05–0.50 wt.% Mn, 0.80–2.00 wt.% Mg, up to 0.20 wt.% Cr, up to 0.20 wt.% Zn, up to 0.15 wt.% Ti, up to 0.15 wt.% impurities, and Al, wherein the aluminum alloy comprises less than 20 wt.% primary aluminum, and wherein the aluminum alloy comprises Mg2Si phase particles present in an amount of 0.8 wt.% to 3.0 wt.%.

[0095] Note 2 refers to any of the aluminum alloys described above or below, which contains 0.30–0.80 wt.% Si, 0.20–0.40 wt.% Fe, 0.10–0.50 wt.% Cu, 0.05–0.50 wt.% Mn, 0.85–1.60 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities, and Al.

[0096] Note 3 refers to any of the aluminum alloys described above or below, which contains 0.30–0.50 wt.% Si, 0.20–0.40 wt.% Fe, 0.30–0.50 wt.% Cu, 0.05–0.20 wt.% Mn, 1.4–1.60 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities, and Al.

[0097] Note 4 refers to any of the aluminum alloys described above or below, which contains 0.50–0.70 wt.% Si, 0.20–0.40 wt.% Fe, 0.30–0.50 wt.% Cu, 0.20–0.40 wt.% Mn, 0.85–1.10 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities, and Al.

[0098] Note 5 refers to any of the aluminum alloys described above or below, which includes recycled aluminum alloy scrap, wherein the recycled aluminum alloy scrap comprises one or more of the following: up to 15 wt.% of 3xxx series recycled aluminum alloy scrap, up to 30 wt.% of 5xxx series recycled aluminum alloy scrap, up to 70 wt.% of 6xxx series recycled aluminum alloy scrap, or up to 30 wt.% of mixed EOL aluminum alloy scrap.

[0099] Description 6 refers to any of the aluminum alloys described above or below, which contain soluble Q phase particles, wherein after solution heat treatment, the aluminum alloy contains less than 1 wt.% of Q phase particles.

[0100] Note 7 refers to any of the aluminum alloys described above or below, wherein the ratio of α-Al(FeMn)Si phase particles to Mg2Si phase particles is 9:1 or greater.

[0101] Note 8 refers to any of the aluminum alloys described above or below, wherein the total amount of Fe, Mn and Cr is at least 0.5 wt.%.

[0102] Note 9 refers to any of the aluminum alloys described above or below, wherein the aluminum alloy has a yield strength of 220 MPa to 300 MPa under T8x tempering.

[0103] Note 10 refers to any of the aluminum alloys described above or below, wherein the aluminum alloy is pre-strained.

[0104] Note 11 refers to any of the aluminum alloys described above or below, wherein the aluminum alloy is subjected to T4 tempering, T6 tempering, or T8x tempering.

[0105] Note 12 refers to any of the aluminum alloys described above or below, wherein the strain of the aluminum alloy is 0.25% to 30%, and the aluminum alloy is substantially free of type A Lüders lines.

[0106] Note 13 refers to any of the aluminum alloys described above or below, wherein the aluminum alloy exhibits an increase in yield strength from 170 MPa to 270 MPa after being subjected to a baking cycle at a temperature of 140°C to 180°C for 10 to 30 minutes.

[0107] Description 14 is a method for producing an aluminum alloy, the method comprising casting an aluminum alloy to form a cast product, wherein the aluminum alloy comprises 0.30–0.80 wt.% Si, 0.20–0.40 wt.% Fe, 0.10–0.50 wt.% Cu, 0.05–0.50 wt.% Mn, 0.80–1.60 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities and Al, wherein the aluminum alloy comprises less than 20 wt.% primary aluminum; homogenizing the cast product; hot rolling the cast product to produce a hot-rolled product; cold rolling the hot-rolled product to produce a rolled product of final specifications; and solution heat treating the rolled product of final specifications.

[0108] Note 15 is any of the methods described above or subsequently, further comprising aging the final specification rolled product to T tempering.

[0109] Note 16 is any of the methods described above or below, wherein the T tempering is T4 tempering, T6 tempering, or T8x tempering.

[0110] Note 17 is any of the methods described above or subsequently, further including pre-straining the final specification rolled product after aging.

[0111] Note 18 is any of the methods described above or below, wherein the cast product is cast from an aluminum alloy comprising one or more of the following: Twitch, 5xxx aluminum alloy, 6xxx aluminum alloy, or tank material.

[0112] Description 19 is any of the methods described above or below, wherein the final specification rolled product contains Q phase particles prior to solution heat treatment, and wherein the final specification rolled product is solution heat treated at a temperature of 500°C to 580°C for up to 1 minute to dissolve the Q phase particles, and the final specification rolled product is substantially free of Q phase particles after solution heat treatment.

[0113] Description 20 is any of the methods described above or below, wherein the final specification rolled product contains Mg2Si phase particles prior to solution heat treatment, and wherein the final specification rolled product is subjected to solution heat treatment at a temperature of 500°C to 600°C for 5 to 30 minutes to dissolve at least half of the Mg2Si phase particles, and after the solution heat treatment, the final specification rolled product contains 0.8 wt.% to 3 wt.% of Mg2Si phase particles.

[0114] Example Example 1 The aluminum alloys described herein can be prepared from a mixture of 5xxx / 6xxx series aluminum alloy scrap and other recycled aluminum alloy scrap sources, which contain higher levels of alloying elements (Fe, Mn, Cr, and Zn) and Mg compared to conventional AA6014, AA6111, and AA6451 aluminum alloys. Exemplary compositions of the aluminum alloys described herein are listed in Table 6.

[0115] *All values ​​are expressed in wt.%.

[0116] The aluminum alloy compositions of Example Alloys A and B are designed to be produced from a variety of recycled aluminum alloy scrap, including 3xxx series recycled aluminum alloy scrap, 5xxx series recycled aluminum alloy scrap, 6xxx series recycled aluminum alloy scrap, and / or mixed EOL recycled aluminum alloy scrap. Table 7 summarizes the calculations used to determine the recycled content of Example Alloys A and B compared to AA5182. As can be seen from the calculations in Table 6, Example Alloy B can be produced from a total of approximately 95 wt.% of various recycled aluminum alloy scrap and 5 wt.% of primary aluminum, while Example Alloy A can be produced from 75 wt.% to 80 wt.% of recycled aluminum alloy scrap and 15 wt.% of primary aluminum.

[0117] Example 2 The recycled aluminum alloy scrap sources provided in Table 7 were melted to cast ingots of example alloys A and B having the compositions provided in Table 5. One ingot was produced for example alloy A, and two ingots were produced for example alloy B. The ingots of example alloys A and B were milled and then homogenized in a two-step homogenization process. In the first step, the milled ingots were heated to 560°C and immersed for 19 hours. In the second step, the ingots were cooled to 540°C and then immersed for approximately 2 hours before starting hot rolling from the ingots to a 4.5 mm gauge. The exit temperature of the hot-rolled ingots was 320°C. The hot-rolled products were coiled at an exit temperature of 320°C. Figure 1A-1C and Figure 1D-1F Example alloy A is shown. Figure 1A-1C ) and example alloy B ( Figure 1D-1F The re-rolled microstructure spans the re-rolling width at edge 1, center, and edge 2. Both re-rolled sections contain Mg₂Si and iron-containing particles up to 10 μm in size. Compared to the re-rolled section of Example Alloy B, Example Alloy A contains a greater number of particles. The large number of particles in Example Alloy A is consistent with its higher Mg content, which, without theoretical limitation, promotes the formation of insoluble Mg₂Si particles.

[0118] Both Example Alloy B and Example Alloy A were cold rolled in two passes to a final gauge of 0.9 mm. Example Alloy A coil was solution-treated at 560°C, rapidly cooled, and coiled at a rewinding temperature of 80°C. Example Alloy B coil was solution-treated at two temperatures, first at 535°C and then at 550°C, and coiled at a rewinding temperature of 80°C.

[0119] Figure 2A-2B Example alloy A is shown. Figure 2A ) and example alloy B ( Figure 2B The polished microstructure of the sheet sample before solution heat treatment. Figure 2C-2D Example alloy A is shown. Figure 2C ) and example alloy B ( Figure 2D The polished microstructure of the sheet sample after solution heat treatment is shown. The cold-rolled sample of Example Alloy A, before continuous annealing and solution heat treatment (SHT), exhibits coarser Mg2Si particles compared to the corresponding sample of Example Alloy B. Furthermore, for both Example Alloy A and Example Alloy B, the particle structure remained unchanged after SHT, suggesting, without theoretical constraints, that the particles observed before SHT were insoluble and remained unaffected after SHT.

[0120] Particles before and after SHT were extracted from the matrix and analyzed using X-ray diffraction. Figure 3AThe X-ray diffraction patterns of the sample of example alloy B before and after SHT are shown. Figure 3B X-ray diffraction patterns of samples of Example Alloy A before and after solution heat treatment (SHT) are shown. In Example Alloy A, the sample before SHT contained α-AlFeSi, Q, Al₂CuMg, and Mg₂Si particles, while the sample after SHT showed only α-AlFeSi and Mg₂Si particles. The Q phase diffraction lines were absent in the sample after SHT, indicating that the Q and Al₂CuMg particles dissolved in the matrix during solution heat treatment. The sample of Example Alloy B before SHT contained α-Al(Fe, Mn, Cu)Si, Q, and Mg₂Si particles, while the particle extract after SHT showed no Q phase particles.

[0121] The relative contents of each phase in the sample of alloy A before and after SHT are determined by... Figure 4A As shown. The relative contents of each phase in the sample of example alloy B before and after SHT are determined by... Figure 4B As shown, α-Al(Fe,Mn)Si particles are the most dominant phase in all samples. In example alloy A, the Al2CuMg and Q phases are completely dissolved in the solid solution, and the Mg2Si fraction decreases. Due to the excess Mg in example alloy A, most Mg2Si particles are insoluble. In example alloy B, all fine Q phases and Mg2Si particles are dissolved during the solution heat treatment, and only nearly spherical coarse Mg2Si and Fe,Mn-containing particles remain in the matrix.

[0122] Based on particle analysis, both example alloy A and example alloy B contain a large number of Fe and Mn-containing particles and dispersions. Hardening can be achieved by the precipitation of the Al2CuMg / Q phase in example alloy A and the precipitation of the Mg2Si / Q phase in example alloy B, respectively.

[0123] Example 3 The mechanical properties of example alloys A and B were further investigated. The ASTM tensile properties of example alloys A and B, as well as their ASTM tensile properties after 30 days of natural aging, along with the ASTM tensile properties of AA5182 and AA6451 coils, are summarized in Table 8. In Table 8, YS represents the yield strength, UTS represents the ultimate tensile strength, El(U) represents the uniform elongation, El(T) represents the tensile elongation, and n(10-20%) represents the strain hardening exponent at 10-20% strain.

[0124] Example alloy A and example alloy B both have R values ​​in all samples and directions. 10 The value is comparable to AA5182, while R...45 The value is surprisingly higher than that of the regular X621 inner alloy.

[0125] Figure 5A The engineering stress-strain curves of the sheet cast from AA5182 are shown in the longitudinal, transverse and diagonal directions. Figure 5B The engineering stress-strain curves of a sheet cast from Example Alloy B are shown in the longitudinal, transverse, and diagonal directions, respectively. Figure 5C The engineered stress-strain curves for sheets cast from Example Alloy A are shown in the longitudinal, transverse, and diagonal directions. Alloy AA5182 exhibits undesirable Type A Lüders effects and serrations at higher strains, which were not observed in the curves of Example Alloy B and Example Alloy A. Example Alloy A exhibits serrations at elongation exceeding 5%. Typically, Example Alloy B follows the stress-strain curve of AA5182 at up to 10% elongation and then remains below that of AA5182.

[0126] Figure 6 Natural aging curves of sample alloy A and sample alloy B sheets after solution heat treatment at 550 °C and 535 °C are shown. As expected, the yield strength (YS) of the sheet solution heat-treated at 550 °C is higher than that of the sheet solution heat-treated at 535 °C. Although, without theoretical constraints, the slopes of the two curves are similar, indicating that the rate of increase in YS is consistent with the slow natural aging response and is independent of the solution treatment temperature. Therefore, without theoretical constraints, the maximum YS can be adjusted according to the choice of solution heat treatment temperature without affecting the aging kinetics. The natural aging of sample alloy A is very slow and remains stable during long-term aging.

[0127] The YS of the formed part is the cumulative result of the strength increase due to forming, precipitation hardening, and strain recovery during paint curing. The forming operation in the laboratory was simulated by a 2% uniaxial strain, which, together with the net increase in YS due to precipitation hardening minus the strain energy loss, is referred to in this paper as the paint response. The overall paint response depends on the paint curing temperature and increases with both the paint curing temperature and time. Figure 7A The example alloy B sheet (535°C SHT) is shown after aging for 20 minutes at 140°C, 160°C and 180°C. Figure 7B The example alloy B sheet (550°C SHT) is shown after aging for 20 minutes at 140°C, 160°C and 180°C. Figure 7CThe example alloy A sheet (560°C SHT) is shown after aging at 140°C, 160°C, and 180°C for 20 minutes. Unlike typical automotive 6xxx series products, example alloy B exhibits a paint-baking response of 173 MPa at 140°C, and a paint-baking response exceeding 240 MPa after coil solution heat treatment at 550°C and aging at 180°C for 20 minutes.

[0128] Figure 8A The high-temperature aging of example alloy B (535°C SHT) at higher temperatures is shown. Figure 8B The high-temperature aging of example alloy B (550°C SHT) at a higher temperature is shown. Figure 8C The high-temperature aging of Example Alloy A (560°C SHT) at higher temperatures is shown. Example Alloy B exhibits a rapid increase in YS during high-temperature aging, which is beneficial for automotive exterior panel applications, particularly at 160°C and 140°C. Example Alloy A also demonstrates a rapid response, but its hardenability is less than that of the Example Alloy B variant.

[0129] Unrestricted by theory, it is believed that the rapid aging response of alloy example B at high temperatures is related to the precipitation of Q(AlCuMgSi) along with Mg2Si phase particles, which is the opposite of conventional 6xxx series alloys hardened by Mg2Si(Cu).

[0130] Two samples of each example alloy A and example alloy B, tempered at T82, were taken from the inner diameter (ID) and outer diameter (OD) of the coil, and their ASTM tensile properties are summarized in Table 9. In Table 9, YS represents the yield strength, UTS represents the ultimate tensile strength, E1(U) represents the uniform elongation, and E1(T) represents the tensile elongation.

[0131] Example 4 To evaluate the formability of Example Alloy B, a coil of Example Alloy B was solution heat treated on a continuous heat treatment line (HTL), with the first half at 550°C and the second half at 535°C. Figures 9A-9B The longitudinal full-thickness polished and etched microstructures of an example alloy B coil solution-treated at 560 °C are shown. The polished microstructure reveals coarse (Fe,Mn)-containing and coarse undissolved Mg₂Si particles within the matrix. The through-thickness grain structure of the coil is finer than that of typical internal materials, which (not limited by theory) is related to the presence of numerous constituent phases, undissolved Mg₂Si, and Mn-containing dispersions in the microstructure.

[0132] Two variants of the example alloy B, which underwent solution heat treatment at 535°C and 550°C, were formed into door inner panels using a stamping press. Figure 10A The blanks of the shape shown were manually re-lubricated with a DC290 before stamping. The edges and corners of the die were also lubricated with a DC290 before stamping. The die was designed to produce blanks of the shape shown. Figure 10B The stamped part shown has four corners, designed to study the severity of forming. For example, corners 1 and 2 are typical radii for an inner door panel, while corners 3 and 4 represent extreme conditions in terms of radius, forming depth, and associated strain.

[0133] Table 10 summarizes the stamping test matrix used to evaluate the formability of Example Alloy B, as well as Example Alloys A and AA5182-O. Two variants of Example Alloy B successfully formed all four corners of the stamped part under edge forces of 100 and 110 bar.

[0134] Forming tests were conducted using the conditions listed in Table 10. It is believed that the improved formability of the example alloy is related to the insoluble particles, which help to disperse slip and improve formability.

[0135] To produce an example Alloy B coil with properties comparable to AA5754-O in 1.5 mm diameter, a coil was solution heat-treated at two temperatures: the first half at 520°C and the second half at 530°C, with a rewinding temperature of 80°C on the HTL. Samples of the coil were taken from the pretreatment line and tested after 9 days of natural aging. The tensile properties from both halves of the coil are listed in Table 11, and the paint response is listed in Table 12. Table 11 shows that the tensile properties of the example Alloy B at both halves are comparable to those of the 1.5 mm diameter AA5754-O production coil. In Table 11, YS represents yield strength, UTS represents ultimate tensile strength, El (U) represents uniform elongation, El (T) represents tensile elongation, n(10-20%) represents strain hardening exponent at 10-20% strain, R(10) represents plastic strain ratio at 10% strain, and average R(10) represents plastic strain ratio in all directions at 10% strain.

[0136] Interestingly, example alloy B still exhibits a significant hardening response despite solution heat treatment at 520°C and 530°C, which could allow for thinning.

[0137] Example 5 Example alloys C and D comprise the aluminum alloy compositions shown in Table 13. Each of Example Alloys C and D was cast to produce ingots, homogenized, and then hot-rolled to produce coils with a specification thickness of 4.5 mm. The hot-rolled coils were cold-rolled to a final specification thickness of 1 mm and subjected to continuous annealing and solution heat treatment. Example Alloy D was solution-treated at approximately 560 °C and coiled at a coiling temperature of approximately 80 °C. Example Alloy C was solution-treated at approximately 525 °C and coiled at a coiling temperature of approximately 80 °C at a linear speed of 60 m / min. The solution treatment of Example Alloy C was approximately 25% faster than that of Example Alloy D. The solution treatment conditions for Example Alloys C and D were different to compare T4 and baking performance (5% pre-strain and heating at approximately 170 °C for approximately 20 min). As shown in Tables 14 and 15, by appropriately selecting the solution treatment conditions, Example Alloy C exhibited mechanical properties within the acceptable range (e.g., + / - 5%) of Example Alloy D.

[0138] *All values ​​are expressed in wt.%.

[0139] Table 14 provides the Japanese Industrial Standard (JIS) mechanical properties of example alloys C and D after 21 days of natural aging. In Table 14, YS represents the yield strength, UTS represents the ultimate tensile strength, E1(U) represents the uniform elongation, E1(T) represents the tensile elongation, n(4-6%) represents the strain hardening exponent at 4-6% strain, n(10%) represents the strain hardening exponent at 10% strain, and R(9-11) represents the plastic strain ratio at 9-11% strain. The tensile test data in Table 14 show that the YS, UTS, and elongation values ​​of example alloy C are slightly lower than those of example alloy D, while other parameters such as N and R values ​​are very similar.

[0140] Table 15 provides the mechanical properties of example alloys C and D after 21 days of natural aging, 5% pre-strain, and aging at approximately 170°C for approximately 20 minutes. In Table 15, YS represents the yield strength, UTS represents the ultimate tensile strength, and E1(T) represents the tensile elongation. Table 14 shows that, although the YS after 21 days of aging is lower as shown in Table 13, the YS of example alloy C is comparable to that of example alloy D. This data indicates that example alloy C has sufficient versatility to provide a wide range of performance combinations while achieving higher solution treatment productivity and equivalent baking paint strength.

[0141] All patents, publications, and abstracts cited above are incorporated herein by reference in their entirety. Various embodiments of the invention have been described to achieve the various objectives of the invention. It should be understood that these embodiments are for illustrative purposes only. Various modifications and alterations will be apparent to those skilled in the art without departing from the spirit and scope of the invention as defined in the following claims.

Claims

1. An aluminum alloy comprising 0.30–0.80 wt.% Si, 0.20–0.50 wt.% Fe, 0.10–0.60 wt.% Cu, 0.05–0.50 wt.% Mn, 0.80–2.00 wt.% Mg, up to 0.20 wt.% Cr, up to 0.20 wt.% Zn, up to 0.15 wt.% Ti, up to 0.15 wt.% impurities, and Al, wherein the aluminum alloy is produced from less than 20 wt.% primary aluminum; The aluminum alloy contains Mg2Si phase particles present in an amount of 0.8 wt.% to 3.0 wt.%; and The weight ratio of Mg content to Si content is greater than 1:

1.

2. The aluminum alloy according to claim 1, wherein the aluminum alloy comprises 0.30–0.80 wt.% Si, 0.20–0.40 wt.% Fe, 0.10–0.50 wt.% Cu, 0.05–0.50 wt.% Mn, 0.85–1.60 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities, and Al.

3. The aluminum alloy according to claim 1, wherein the aluminum alloy comprises 0.30–0.50 wt.% Si, 0.20–0.40 wt.% Fe, 0.30–0.50 wt.% Cu, 0.05–0.20 wt.% Mn, 1.4–1.60 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities, and Al.

4. The aluminum alloy according to claim 1, wherein the aluminum alloy comprises 0.50–0.70 wt.% Si, 0.20–0.40 wt.% Fe, 0.30–0.50 wt.% Cu, 0.20–0.40 wt.% Mn, 0.85–1.10 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities, and Al.

5. The aluminum alloy according to claim 1, wherein the aluminum alloy is produced from recycled aluminum alloy scrap, wherein the recycled aluminum alloy scrap comprises one or more of the following: up to 15 wt.% of 3xxx series recycled aluminum alloy scrap, up to 30 wt.% of 5xxx series recycled aluminum alloy scrap, up to 70 wt.% of 6xxx series recycled aluminum alloy scrap, or up to 30 wt.% of mixed EOL aluminum alloy scrap.

6. The aluminum alloy according to claim 1, wherein the aluminum alloy comprises soluble Q phase particles, wherein after solution heat treatment of the aluminum alloy, the aluminum alloy comprises less than 1 wt.% of Q phase particles.

7. The aluminum alloy according to claim 1, wherein the ratio of α-Al(FeMn)Si phase particles to Mg2Si phase particles is 9:1 or greater.

8. The aluminum alloy according to claim 1, wherein the total amount of Fe, Mn and Cr is at least 0.5 wt.%.

9. The aluminum alloy according to claim 1, wherein the aluminum alloy has a yield strength of 220 MPa to 300 MPa under T8x tempering.

10. The aluminum alloy according to claim 1, wherein the aluminum alloy is pre-strained.

11. The aluminum alloy according to claim 1, wherein the aluminum alloy is subjected to T4 tempering, T6 tempering or T8x tempering.

12. The aluminum alloy of claim 1, wherein the strain of the aluminum alloy is 0.25% to 30%, and the aluminum alloy is substantially free of type A Lüders lines.

13. The aluminum alloy according to claim 1, wherein the aluminum alloy exhibits an increase in yield strength from 170 MPa to 270 MPa after being subjected to a baking cycle at a temperature of 140°C to 180°C for 10 to 30 minutes.

14. The aluminum alloy according to claim 1, wherein the weight ratio of Mg content to Si content is 3:1 to 5:

1.

15. A method for producing aluminum alloy, the method comprising: Casting an aluminum alloy to form a cast product, wherein the aluminum alloy comprises 0.30 – 0.80 wt.% Si, 0.20 – 0.40 wt.% Fe, 0.10 – 0.50 wt.% Cu, 0.05 – 0.50 wt.% Mn, 0.80 – 1.60 wt.% Mg, up to 0.10 wt.% Cr, up to 0.10 wt.% Zn, up to 0.10 wt.% Ti, up to 0.15 wt.% impurities, and Al, wherein the aluminum alloy comprises less than 20 wt.% primary aluminum; Homogenize the cast product; The hot-rolled castings are used to produce hot-rolled products. Cold rolling is used to produce hot-rolled products to produce rolled products of final specifications; as well as The rolled product of the final specification is subjected to solution heat treatment.

16. The method of claim 15, further comprising aging the final specification rolled product to T tempering.

17. The method of claim 16, wherein the T tempering is T4 tempering, T6 tempering, or T8x tempering.

18. The method of claim 15 or 16, further comprising pre-straining the final specification rolled product after aging.

19. The method of claim 15, wherein the cast product is cast from an aluminum alloy comprising one or more of the following: Twitch, 5xxx aluminum alloy, 6xxx aluminum alloy, or can body material.

20. The method of claim 15, wherein the final-size rolled product contains Q-phase particles prior to solution heat treatment, and wherein the final-size rolled product is subjected to solution heat treatment at a temperature of 500°C to 580°C for up to 1 minute to dissolve the Q-phase particles, and the final-size rolled product is substantially free of Q-phase particles after the solution heat treatment.

21. The method of claim 15, wherein the final-size rolled product comprises Mg2Si phase particles prior to solution heat treatment, and wherein the final-size rolled product is subjected to solution heat treatment at a temperature of 500°C to 600°C for 5 to 30 minutes to dissolve at least half of the Mg2Si phase particles, and the final-size rolled product comprises 0.8 wt.% to 3 wt.% of Mg2Si phase particles after the solution heat treatment.